Development of a Web-Based Program for Cross-Calibration and Record Management of Radiation Measuring Equipment - Park, So Hyun; Lee, Rena; Kim, Kyubo; Ahn, Sohyun; Lim, Sangwook; Cho, Samju (Progress in Medical Physics, 2019)
Purpose: To manage radiation measurement equipment, a web-based management program has been developed in this study. Materials and Methods: This program is based on a web service and Java Server Pages (JSP) and employs compatibility and accessibility. Results: The first step in the workflow has been designed to create accounts for each user or organization and to log in. The program consists of two parts: fields for listed instruments, and measurement information. The instruments for measuring radiation listed in this program are as follows: ionization chambers, survey meters, thermometers, barometers, electrometers, and phantoms. Instrument properties can be put in the recording fields and browsing for associated instruments can be performed. The main part of the program is the cross-calibration for each ion chamber. For instance, the ionization chamber to be used as a relative dosimeter can be registered by cross-calibration data with a reference chamber calibrated by an accredited laboratory. This program supports methods using the central axis transfer theory for cross-calibration for the ionization chambers. The reference and field ionization chambers were placed in a solid water phantom along the beam central axis at two different depths, and then the positions were switched. Each measured value was used for calculating the cross-calibration factor. Conclusions: B ecause m any i nstruments a re u sed a nd m anaged i n r adiation o ncology departments, systematic, traceable recording is very important. The web-based program developed in this study is expected to be used effectively in the maintenance of radiation measurement instruments. KCI Citation Count: 0